9-2x(x+4)-10(25-x+4)=5-3x-4(x+1)

Simple and best practice solution for 9-2x(x+4)-10(25-x+4)=5-3x-4(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-2x(x+4)-10(25-x+4)=5-3x-4(x+1) equation:


Simplifying
9 + -2x(x + 4) + -10(25 + -1x + 4) = 5 + -3x + -4(x + 1)

Reorder the terms:
9 + -2x(4 + x) + -10(25 + -1x + 4) = 5 + -3x + -4(x + 1)
9 + (4 * -2x + x * -2x) + -10(25 + -1x + 4) = 5 + -3x + -4(x + 1)
9 + (-8x + -2x2) + -10(25 + -1x + 4) = 5 + -3x + -4(x + 1)

Reorder the terms:
9 + -8x + -2x2 + -10(25 + 4 + -1x) = 5 + -3x + -4(x + 1)

Combine like terms: 25 + 4 = 29
9 + -8x + -2x2 + -10(29 + -1x) = 5 + -3x + -4(x + 1)
9 + -8x + -2x2 + (29 * -10 + -1x * -10) = 5 + -3x + -4(x + 1)
9 + -8x + -2x2 + (-290 + 10x) = 5 + -3x + -4(x + 1)

Reorder the terms:
9 + -290 + -8x + 10x + -2x2 = 5 + -3x + -4(x + 1)

Combine like terms: 9 + -290 = -281
-281 + -8x + 10x + -2x2 = 5 + -3x + -4(x + 1)

Combine like terms: -8x + 10x = 2x
-281 + 2x + -2x2 = 5 + -3x + -4(x + 1)

Reorder the terms:
-281 + 2x + -2x2 = 5 + -3x + -4(1 + x)
-281 + 2x + -2x2 = 5 + -3x + (1 * -4 + x * -4)
-281 + 2x + -2x2 = 5 + -3x + (-4 + -4x)

Reorder the terms:
-281 + 2x + -2x2 = 5 + -4 + -3x + -4x

Combine like terms: 5 + -4 = 1
-281 + 2x + -2x2 = 1 + -3x + -4x

Combine like terms: -3x + -4x = -7x
-281 + 2x + -2x2 = 1 + -7x

Solving
-281 + 2x + -2x2 = 1 + -7x

Solving for variable 'x'.

Reorder the terms:
-281 + -1 + 2x + 7x + -2x2 = 1 + -7x + -1 + 7x

Combine like terms: -281 + -1 = -282
-282 + 2x + 7x + -2x2 = 1 + -7x + -1 + 7x

Combine like terms: 2x + 7x = 9x
-282 + 9x + -2x2 = 1 + -7x + -1 + 7x

Reorder the terms:
-282 + 9x + -2x2 = 1 + -1 + -7x + 7x

Combine like terms: 1 + -1 = 0
-282 + 9x + -2x2 = 0 + -7x + 7x
-282 + 9x + -2x2 = -7x + 7x

Combine like terms: -7x + 7x = 0
-282 + 9x + -2x2 = 0

Begin completing the square.  Divide all terms by
-2 the coefficient of the squared term: 

Divide each side by '-2'.
141 + -4.5x + x2 = 0

Move the constant term to the right:

Add '-141' to each side of the equation.
141 + -4.5x + -141 + x2 = 0 + -141

Reorder the terms:
141 + -141 + -4.5x + x2 = 0 + -141

Combine like terms: 141 + -141 = 0
0 + -4.5x + x2 = 0 + -141
-4.5x + x2 = 0 + -141

Combine like terms: 0 + -141 = -141
-4.5x + x2 = -141

The x term is -4.5x.  Take half its coefficient (-2.25).
Square it (5.0625) and add it to both sides.

Add '5.0625' to each side of the equation.
-4.5x + 5.0625 + x2 = -141 + 5.0625

Reorder the terms:
5.0625 + -4.5x + x2 = -141 + 5.0625

Combine like terms: -141 + 5.0625 = -135.9375
5.0625 + -4.5x + x2 = -135.9375

Factor a perfect square on the left side:
(x + -2.25)(x + -2.25) = -135.9375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 100-4x=41x+15 | | 20=-4t | | 7-9x=62-44x | | 2t+4=16 | | 28u^48-22u^8vy^7= | | 2236000-17740x=2324700 | | 6x^2=6x | | x+1=39 | | 24-(x+3)=12+2(9-2x) | | 4x-5=11-82 | | -x-2y=-3 | | 30=-6t | | 3=-6t | | x^3-3x^2+6x-12=0 | | (2x+4)(4x+6)(6x+8x)=0 | | 2/3a=12-4 | | 49=-x | | x^5=1.25 | | 4x^2+23x+15x=0 | | 3m/2-2/4=9/2-m | | -4b^2+36=0 | | x-7(2x+1)=2(6-5x)-13 | | (6x+7)-(-13x+8)=0 | | 25=x+4 | | (2x+7)(x+1)=28-2 | | -3x-3(z-3)=3 | | x^2-7x-19=-6+1 | | 5-(4x+6)=3x+(7-4x) | | -8=-8+x | | 1/3+2/3m=1/3m-2/3 | | 2(2+3)= | | t=t^2-4t+3 |

Equations solver categories